Mechanical characterization of arhar biomass based porous nano activated carbon polymer composites. Issue 8 (23rd April 2020) - Om Prakash, Minugu; Gujjala, Raghavendra; Panchal, Manoj; Ojha, Shakuntala
Abstract: Activated carbon material was synthesized by two stage pyrolysis and chemical activation method using arhar fiber biomass as precursor. The effect of activation temperature on the characteristics of activated carbon materials was explored. Temperatures of 700°C, 800°C, and 900°C were used for the production of activated carbon materials. BET surface area, pore size, and pore volume were studied using N2 adsorption analysis. Activated carbon prepared at 800°C temperature was found to be effective; exhibited 504.6 m 2 /g surface area and pore volume of 0.245569 cm 3 /g with micropores of less than 20 Å diameter. XRD analysis of the material exhibited broad and sharp peaks in the range of 18 to 30 (2 θ ), confirming amorphous structure. From thermogravimetric analysis, it was noticed that activated carbon has high thermal stability. It was left with 62% of residual mass when subjected to 1400°C temperature. Activated carbon material synthesized at 800°C was used as filler while epoxy functioned as matrix material for fabrication of composites. The effect of filler loading on the tensile strength of composites was studied. Tensile strength of composite material increased with addition of filler loading. It was observed that composite with 2% filler loading had a maximum tensile strength of 56 MPa.